2023
DOI: 10.1289/ehp11851
|View full text |Cite
|
Sign up to set email alerts
|

A State-of-the-Science Review on High-Resolution Metabolomics Application in Air Pollution Health Research: Current Progress, Analytical Challenges, and Recommendations for Future Direction

Abstract: Background: Understanding the mechanistic basis of air pollution toxicity is dependent on accurately characterizing both exposure and biological responses. Untargeted metabolomics, an analysis of small-molecule metabolic phenotypes, may offer improved estimation of exposures and corresponding health responses to complex environmental mixtures such as air pollution. The field remains nascent, however, with questions concerning the coherence and generalizability of findings across studies, study des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 105 publications
(90 reference statements)
1
17
0
Order By: Relevance
“…Metabolomics is the systemic study of all metabolites associated with exogenous exposure and endogenous processes, and has emerged as an innovative and powerful analytical platform in environmental epidemiology. , Recent investigations demonstrate the applicability of using metabolomics as a central platform to link human exposure with internal dose and biological response. Specifically, an increase in circulating concentrations of PFAS has been consistently associated with several endocrine disruption- and oxidative stress-related pathways. ,, In one of our recent metabolome-wide association studies (MWAS), we also identified and verified several biomechanisms and biomarkers mediating the association between serum PFAS concentrations and fetal growth restriction . Moreover, in two separate analyses within the same pregnant population, we found an inverse association between prenatal exposure to PFAS, modeled as single chemicals and a mixture, with fetal growth measures. , …”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Metabolomics is the systemic study of all metabolites associated with exogenous exposure and endogenous processes, and has emerged as an innovative and powerful analytical platform in environmental epidemiology. , Recent investigations demonstrate the applicability of using metabolomics as a central platform to link human exposure with internal dose and biological response. Specifically, an increase in circulating concentrations of PFAS has been consistently associated with several endocrine disruption- and oxidative stress-related pathways. ,, In one of our recent metabolome-wide association studies (MWAS), we also identified and verified several biomechanisms and biomarkers mediating the association between serum PFAS concentrations and fetal growth restriction . Moreover, in two separate analyses within the same pregnant population, we found an inverse association between prenatal exposure to PFAS, modeled as single chemicals and a mixture, with fetal growth measures. , …”
Section: Introductionmentioning
confidence: 73%
“…Further, our results may be subject to recall bias for specific confounders (e.g., substance use), where participants may be more likely to under-report usage. Lastly, given the purpose of this proof-of-concept analysis is to demonstrate the feasibility and utility of applying mixture analysis in metabolomics application, we used unadjusted p -values for the pathway enrichment analysis due to insufficient power, which is common in environmental metabolomics studies . Despite the use of a less conservative significance cutoff, we identified pathways and metabolites similar to other PFAS MWAS that corrected for multiple comparisons. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the annotated features were associated with NO 2 exposure. Of these 14 compounds, 4 compounds (caffeine, phenylalanine, 2 acyl-carnitines), were also found in our previous work . Our new analysis revealed higher levels of cortisol and cortisone, indoleactic acid (IAA), and indole-3-propionic acid (IPA) associated with TRAP exposure, as well as lower levels of isoleucine (SI Table 4).…”
Section: Resultsmentioning
confidence: 96%
“…Such studies have shown that a period of physical activity has beneficial health effects, although these benefits may be offset by the impact of TRAP exposure on cardiopulmonary and lung function, with increases in inflammatory blood cells observed. However, the underlying biological mechanisms have not been fully elucidated, and classical epidemiological methods cannot accurately ascertain the short-term impacts of exposures to TRAP, largely due to the absence of robust and specific biomarkers. The advent of omics-based high-throughput technologies allows for molecular changes and biological pathways associated with TRAP exposure to be identified at a cellular level, and underlying pathomolecular mechanisms to be mapped more precisely. Metabolomics and transcriptomics provide powerful analytical methods to understand the molecular and biochemical pathways triggering a systemic response that can be observed in the peripheral blood. , Metabolomics systematically investigates metabolites, such as amino acids, fatty acids, and lipids, and their impact on oxidative stress and inflammation pathways, in turn affecting human health and disease risk. , Untargeted metabolomics offers a valuable approach to identifying and quantifying the effect of TRAP exposure on the blood metabolome. ,, Transcriptomics allows the identification of gene expressions that are differentially induced and can be used as exposure biomarkers . Combining metabolomics and transcriptomics obtained from the same samples offers a more comprehensive approach to better understand the biological response and the pathways affected by exposure to TRAP, as it will extend the coverage of the molecules assayed and include a large variety of both endogenous and exogenous molecules.…”
Section: Introductionmentioning
confidence: 99%